2016
DOI: 10.1542/hpeds.2015-0060
|View full text |Cite
|
Sign up to set email alerts
|

Screen Media Use in Hospitalized Children

Abstract: BACKGROUND AND OBJECTIVES: Screen media overuse is associated with negative physical and mental health effects in children. The American Academy of Pediatrics recommends limiting screen media use at home; however, there are no similar guidelines for children’s hospitals. This study was conducted to explore caregiver (parent or other guardian) perceptions about screen media use, compare at-home with in-hospital screen media use, and measure screen use among hospitalized children. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 35 publications
(37 reference statements)
1
22
2
5
Order By: Relevance
“…To our knowledge, only 1 study has been done on the effects of screen time in hospitalized children. 18 In this study, parents reported their children engaging in significantly more screen time (beyond AAP recommendations) in the hospital setting compared to home use. 18 While this study demonstrated the significant role of screen use within the hospital environment, it did not address screen use during the evening to night hours nor in the ICU setting.…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…To our knowledge, only 1 study has been done on the effects of screen time in hospitalized children. 18 In this study, parents reported their children engaging in significantly more screen time (beyond AAP recommendations) in the hospital setting compared to home use. 18 While this study demonstrated the significant role of screen use within the hospital environment, it did not address screen use during the evening to night hours nor in the ICU setting.…”
Section: Introductionmentioning
confidence: 76%
“…AAP recommends that children under the age of 18 months avoid nearly all screen media other than video-chatting with relatives; and for children 18 to 24 months to have less than an hour of parent guided quality screen time. 18 For children 2 to 5 screen use should be limited to 1 hour of high quality programing. In this study, we extrapolated active engaged screen use over the observation period into an estimate of screen time in a 24-hour period ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers in one study found that screen media was used in 80.3% of observations of awake hospitalized children, and children directly attended to the screen in nearly 50% of observations. 21 Screen overuse is associated with negative physical and mental health effects in children, such as interference with sleep, eating, and mood. 22 Poetry offers a beneficial screenless activity that allows children to spend time away from television and iPads.…”
Section: )Screenless Activitymentioning
confidence: 99%